Is “E-Health Literacy” Related To “Coronavirus-Related Health Literacy”: Facilitating dissemination of health information through social media in the post-COVID-19 ERA - Maryam Kazerani; Sana Zandkarimi; Mahdieh Mottaghi; Marzieh Kazerani; Sara Jambarsang (Asia Pacific Journal of Health Management)
To use electronic health information resources correctly and effectively, a set of skills and capabilities called "electronic health literacy" is needed. . This study aims to assess the E-health literacy of patients with COVID-19 in a university-affiliated education hospital and its relationship with coronavirus-related health. Using convenience sampling, 190 patients were selected, filling out the eHEALS (eHealth literacy scale) questionnaire with their consent.